Prevalence of hearing impairment and language and cognition delay in very low birth weight babies and their risk factors - Chaudhuri, Saugata; Mukherjee, Suchandra; Bose, Tanmoy Kumar; Chowdhury, Turna Roy (Asian Journal of Medical Sciences, 2021)
Background: Very low birth weight infants are at increased risk of language, cognition delay and also hearing impairment disorder. Identification is essential for early intervention. Aims and Objectives: To estimate the burden of language, cognition delay and hearing impairment at 24 months of corrected gestation and to test the association of examination at 6 months and 12 months with the language and cognitive outcome of very low birth weight (VLBW) infants at 24 months and to identify the perinatal and neonatal risk factors for atypical outcome. Materials and Methods: It is a prospective cohort study. Consecutive 120 VLBW infants were enrolled in a single centre level III neonatal unit of a teaching hospital. Hearing assessment was done before discharge and 3 monthly. Language and cognitive assessment was done by DASII Scale neu at 6 months and BSIDIII Scale at 12 months and 24 months at neurodevelopmental clinic. Language assessment was further done by REELS-3 Subscale at 24 months. All assessment ages were corrected for prematurity. Results: At 24 months 7.8% infants developed Language delay and 4.7% had cognition delay. Four infants developed cerebral palsy at 24 months. Shock in neonatal period had significant association with suboptimal Hearing, Language and Cognitive outcome at 12 months of corrected gestation. Conclusion: Early anticipation and early identification of abnormal hearing, language and cognitive outcome of VLBW infants can be used as simple and cost-effective measures for preventing long-term morbidity at resource limited countries.